Real Implementation of Fault-Tolerant Sliding Mode Control for a Robot Manipulator - Le, Quang Dan; Kang, Hee-Jun (2018 3rd International Conference on Control, Robotics and Cybernetics (CRC), 2018)
In this paper, an active fault-tolerant sliding mode control of robot manipulator is proposed and real implemented for a 3-DOF robot manipulator. When the unknown actuator faults occur sometime during the robot operation, an external linear state observer is adopted to estimate uncertainties/disturbances and faults. By using this observer, we no need the exact knowledge of the upper bound of faults. Then, the active fault-tolerant sliding mode control with online compensation based on the estimation is proposed. The stability of system was proved by using Lyapunov theory. Finally, the simulation and experimental results for a robot manipulator are shown to illustrate the effectiveness of the proposed control.